2005
DOI: 10.1152/japplphysiol.00932.2004
|View full text |Cite
|
Sign up to set email alerts
|

Plasma from conscious hypoxic rats stimulates leukocyte-endothelial interactions in normoxic cremaster venules

Abstract: . Plasma from conscious hypoxic rats stimulates leukocyte-endothelial interactions in normoxic cremaster venules. J Appl Physiol 99: 290 -297, 2005. First published March 3, 2005 doi:10.1152/japplphysiol.00932.2004.-Systemic hypoxia results in rapid increases in leukocyte-endothelial adherence (LEA) and emigration, vascular permeability, and mast cell activation in several microcirculations. Observations in cremaster muscle suggest that this response is initiated by a mediator released from a distant site (Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 21 publications
8
28
0
Order By: Relevance
“…Conversely, an MCP-1 receptor antagonist blocks alveolar hypoxia-induced systemic inflammation in intact rats. This is consistent with previous observations that AMO depletion prevents alveolar hypoxia-induced systemic inflammation, and that plasma from intact hypoxic rats, but not of AMO-depleted rats, elicits inflammation in normoxic tissues [28,88]. …”
Section: Amos Are Required For Systemic Inflammation Under Alveolar Hsupporting
confidence: 93%
“…Conversely, an MCP-1 receptor antagonist blocks alveolar hypoxia-induced systemic inflammation in intact rats. This is consistent with previous observations that AMO depletion prevents alveolar hypoxia-induced systemic inflammation, and that plasma from intact hypoxic rats, but not of AMO-depleted rats, elicits inflammation in normoxic tissues [28,88]. …”
Section: Amos Are Required For Systemic Inflammation Under Alveolar Hsupporting
confidence: 93%
“…Our previous work provided compelling evidence that the systemic inflammation of hypoxia is not initiated by reduced tissue PO 2 , but rather by a mediator released from AMØ and transported by the circulation (7,8,12,13,16,19). A role for AMØ-borne MCP-1 as the putative mediator was suggested by the recent finding that primary cultures of AMØ, but not of peritoneal MCs or peritoneal macrophages, release MCP-1 within 30 minutes of exposure to hypoxia (16).…”
Section: Discussionmentioning
confidence: 97%
“…The effect of hypoxic rat plasma is not attributable to inflammatory mediators released into plasma by activated MCs or adherent leukocytes of the donor rat. Furthermore, the agents responsible for inflammation are not generated by blood cells (19). (4) A topical application of supernatant from hypoxic AMØ produces the degranulation of MCs, increased leukocyte-endothelial adherence, and increased vascular permeability in the normoxic cremaster (12).…”
mentioning
confidence: 99%
“…This idea is supported by two lines of evidence: first, selective reduction of cremaster PO 2 does not produce mast cell degranulation and inflammation in the cremaster microcirculation unless alveolar PO 2 is also reduced (2, 3); second, plasma obtained from hypoxic rats applied to the normoxic cremaster produces an inflammatory response similar to that elicited by alveolar hypoxia (8). The response to hypoxic rat plasma is not due to inflammatory mediators released into plasma by activated mast cells or adherent leukocytes of the donor rat; furthermore, the agent(s) responsible for the inflammation is not generated by blood cells (8). Further investigation has shown that the putative mediator activates mast cells and initiates an inflammatory cascade that includes activation of the renin-angiotensin (Ang) system (RAS) (9).…”
mentioning
confidence: 94%